Uji UI UX Pada Aplikasi Peduli Lindungi Menggunakan User Experience Questionare (UEQ) di Gedung Perkantoran Gading Serpong - Putra, Rafhidal Lesmana; Rerung, Rintho Rante (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The application called Peduli Protect is a form of government policy to control and overcome various problems that arise due to the Covid-19 pandemic. The Peduli Protect application aims at three main priorities, namely 1) protecting the public in accessing public facilities, 2) tracing people who are indicated to be exposed to Covid-19, and 3) information on mapping the zoning of exposure to Covid-19. One of the testing tools for the Cares Protect Application is the User Experience Questionnaire (UEQ), where the User Experience Questionnaire (UEQ) is used to describe the experience gained by the user or UX for satisfaction and usability in the visual appearance of the application, both text boxes, drop-down lists, and other components or commonly called UI when using App Care Protect device. In this study, the method used is combined, namely qualitative quantitative (where technical data collection is done by distributing questionnaires, where each response to each statement item in the questionnaire has a different assessment area and respondents are also required to fill in their demographic data). The total population in this study is 100 Respondents, and the samples taken of all the total population are 100 respondents too. The formulations in this study are 1) How to evaluate the user experience/UX in using the Peduli Protect Application with User Experience Questionnaire (UEQ)? While the objectives of this study are 1) to determine the results of the evaluation of user experience/UX in using the Cares Protect Application using the User Experience Questionnaire (UEQ). The results of the evaluation of user experience / user experience / UX using User Experience Questionnaire (UEQ) in 6 aspects are attractiveness 0,06; clarity 0,53; efficiency 0,36; accuracy 0,17; stimulation 0,09; and novelty 0,01. This shows that all aspects of the user experience get a negative impression. The results of this study can be used as recommendations for designing the new Peduli Protect application user experience by innovating in various aspects.